Response of the native plant coriandrum (Coriandrum sativumL.) of potassium at increasing concentrations of kinetin (Journal of the College of Basic Education, 2022)
The experiment was conducted in one of the fields of Bob Al-Sham region in Baghdad governorate, during the agricultural season 2012-2013, in order to find out the effect of different levels of potassium at increasing concentrations of kinetin on some phenotypic indicators and some effective medicinal compounds in the local coriander plant (Coriandrum sativum L.), carried out with a design. Randomized Complete Block Design (RCBD) with three replications, as four levels of potassium were used in the experiment, which are (300,150,75,0) kg.h-1, and four concentrations of kinetin, which are (150,100,50,0) mg..l-1. A study of some phenotypic growth indicators (plant height, fresh weight and dry weight) and physiological and effective medicinal compounds in volatile oil.